1998
DOI: 10.1182/blood.v92.7.2527
|View full text |Cite
|
Sign up to set email alerts
|

Early Phagocytosis of Glucose-6-Phosphate Dehydrogenase (G6PD)-Deficient Erythrocytes Parasitized by Plasmodium falciparum May Explain Malaria Protection in G6PD Deficiency

Abstract: In population-based studies it has been established that inherited deficiency of erythrocyte (E) glucose-6-phosphate dehydrogenase (G6PD) confers protection against severe Plasmodium falciparum (P falciparum) malaria. Impaired growth of parasites in G6PD-deficient E in vitro has been reported in some studies, but not in others. In a systematic analysis, we have found that with five different strains ofP falciparum (FCR-3, KI, C10, HB3B, and T9/96), there was no significant difference in either invasion or matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(84 citation statements)
references
References 35 publications
4
80
0
Order By: Relevance
“…It is still not absolutely clear how G6PD deficiency protects against malaria. It is very likely that it is related to the susceptibility of G6PD-deficient red cells to oxidative stress; the observation that deficient red cells undergo phagocytosis by macrophages at an earlier stage than parasitised normal cells (Cappadoro et al, 1998) raises the possibility that, rather as has been suggested for the protective effect mediated by the sicklecell variant, suicidal infection may be at least one protective mechanism (Luzzatto et al, 2001).…”
Section: Red-cell Metabolismmentioning
confidence: 99%
“…It is still not absolutely clear how G6PD deficiency protects against malaria. It is very likely that it is related to the susceptibility of G6PD-deficient red cells to oxidative stress; the observation that deficient red cells undergo phagocytosis by macrophages at an earlier stage than parasitised normal cells (Cappadoro et al, 1998) raises the possibility that, rather as has been suggested for the protective effect mediated by the sicklecell variant, suicidal infection may be at least one protective mechanism (Luzzatto et al, 2001).…”
Section: Red-cell Metabolismmentioning
confidence: 99%
“…Under conditions of oxidative stress, which can cause major haemolysis in G6PD-deficient individuals, growth of Plasmodium seems to be inhibited more consistently (Miller et al, 1984;Golenser et al, 1988). Recent studies by Cappadoro et al (Cappadoro et al, 1998) have shown that G6PD-deficient erythrocytes were more susceptible to phagocytosis by peripheral blood monocytes, particularly at the early ring-stage of infection concomitant to increased binding of IgG and complement C3 to infected erythrocytes. G6PD-deficient cells are more prone to changes in the cell membrane because of low levels of GSH (see Fig.…”
Section: G6pd Deficiency and Malaria Protectionmentioning
confidence: 99%
“…Importantly, the reduced life-span and early removal from the circulation of PK-deficient erythrocytes may, as proposed for haemoglobinopathies and for G6PD deficiency, also result in increased phagocytosis of parasitized red cells early in infection. Whether this is mediated by increased expression of phagocytic markers like complement C3 and IgG, as seems to be the case for alphathalassaemia and G6PD deficiency (Cappadoro et al, 1998;Ayi et al, 2004), remains to be tested.…”
Section: Pyruvate Kinase Deficiency and Malaria Protectionmentioning
confidence: 99%
“…Mechanistically, the increased membrane-bound Hb levels may contribute to a more efficient clearing of parasitized RBCs from the circulation, reducing the incidence of clinical malaria. Constitutively increased levels of membrane-bound Hb may be due to malaria-protective mutations (Cappadoro et al, 1998;Ayi et al, 2004) and persistence of Hb F (Advani et al, 1992;Amaratunga et al, 2011). The increased membrane-bound Hb might be also the mechanistic link for the herein observed positive association between GSH level in the RBC and malaria IR.…”
Section: Oxidative Stress By Malaria In Childhoodmentioning
confidence: 69%
“…A second set of data investigates the shown in vitro generation of oxidative stress exerted by the growing parasite to the RBC membrane (Atamna & Ginsburg, 1993;Skorokhod et al, 2007), oxidizing Hb and producing intracellular membrane-bound haemichromes (Rifkind et al, 1994;Giribaldi et al, 2001;Arese et al, 2005) that cluster band 3, leading to opsonization and phagocytosis of the RBC (Giribaldi et al, 2001;Arese et al, 2005;Pantaleo et al, 2008). The enhanced phagocytosis observed in ring-parasitized RBCs with the sickle-cell trait, glucose-6-phosphate dehydrogenase-deficiency or the thalassaemias, has been proposed as the mechanism underlying the protective effect of those mutations (Cappadoro et al, 1998;Ayi et al, 2004). Similarly, the increased Hb-binding observed in oxidized RBC membranes (Demehin et al, 2001) might add to this mechanism, triggered by reactive oxygen species from activated phagocytes and parasites, unstable Hb or free haem.…”
Section: Oxidative Stress By Malaria In Childhoodmentioning
confidence: 99%